Reconfigurable Periodic Liquid Crystal Defect Array via Modulation of Electric Field. Issue 11 (18th September 2019) - You, Ra; Choi, Yun‐Seok; Shin, Min Jeong; Seo, Min‐Kyo; Yoon, Dong Ki
Abstract: Topological defects in liquid crystal (LC) phases have been considered critical from the areas in topology and self‐assembly, as well as in applications such as optical vortex generation, particle manipulation system, and template for material micropatterning. An approach for generating and modulating various patterns of LC defects is presented in a single cell by varying the electrode configurations. Periodic LC defect arrays including −1 topological defect in the nematic phase can be achieved by simply adjusting crossed electrodes. Specifically, the fourfold symmetric −1 defect pattern is used as a vortex beam generator and a particle trapping agent with control either of the frequency of the applied electric field or the temperature. The approach suggested here would be beneficial to extend the use of LC patterns in lithographic tools and optoelectronic devices. Abstract : Various topological defect arrays are generated in the nematic liquid crystal phase and controlled by applying electric fields made by crossed electrode‐patterns at various temperatures as well as frequencies. The fabricated topological patterns can be used as a vortex beam generator and particle‐trapping/releasing agent. The proposed platform can be widely applied in lithographic applications as well as opto‐electronic devices.